Self Branding of Grobogan District Through Mapping Superior Potential - Astuti, Tri Marhaeni Pudji; Banowati, Eva; Wijaya, Atika; Fajar, Fajar (Jurnal Abdimas, 2023)
Grobogan is one of the largest districts in Central Java which has various areasSelf Branding and sstereotype-its. One of the interesting expressions that seems to betagline is "Purwodadi His City That Became Reality”. This expression triggers the enthusiasm to continue working and shows the existence of Purwodadi City, Grobogan Regency. One of the problems in Grobogan Regency - perhaps also faced by most other districts - is the problemSelf Branding or Personal Branding.Self Branding or personal branding is the ability to shape people's perception of oneself or one's personal perception and what one has to offer professionally now and in the future.Self Branding Grobogan for many years has always been a "bad road".Self Branding This is certainly detrimental to Grobogan Regency. Actually Grobogan has a lot of potential besidesSelf Branding which is detrimental. The problem of changeSelf Branding It's not easy, but it can be done. Awareness of the people of Grobogan district to brand themselves is very necessary. The will of the Grobogan people to want to createSelf Branding andbarandingpositive is very necessary. Grobogan has a lot of superior potential which has so far been little known due to problemsbranding. This problem needs to be addressed, one of which is by "arousing the will of the Grobogan people to want tobranding himself." For this, one thing that can be done is collaboration with universities through community service activities. Problems that can be solved through community service activities are (1) How to instill community understanding about the importance of community serviceSelf Branding (2) How to raise public awareness of what to doSelf Branding by wanting to identify the superior potential that exists in various regions in Grobogan Regency (3) How to map the superior potential that exists in Grobogan Regency as an effortSelf Branding. This service activity aims to foster and instill understanding in the Grobogan community about its importanceSelf Branding as well as mapping the superior potential that exists in Grobogan forSelf Branding.To overcome this problem, activities are carried out in the form of (1) providing outreach, understanding and strengthening the importance of itSelf Branding for Grobogan Regency (2) Instilling the importance of mapping superior potential in various regions in Grobogan (3) Accompanying the creation of superior potential maps in Grobogan Regency. It is hoped that these three service activities can overcome the problemSelf Branding in Grobogan Regency.